Be Cautious with the Precautionary Principle: Evidence from Fukushima Daiichi Nuclear Accident - Matthew Neidell; Shinsuke Uchida; Marcella Veronesi (Institute of Labor Economics (IZA), 2019)
This paper provides a large scale, empirical evaluation of unintended effects from invoking the precautionary principle after the Fukushima Daiichi nuclear accident. After the accident, all nuclear power stations ceased operation and nuclear power was replaced by fossil fuels, causing an exogenous increase in electricity prices. This increase led to a reduction in energy consumption, which caused an increase in mortality during very cold temperatures. We estimate that the increase in mortality from higher electricity prices outnumbers the mortality from the accident itself, suggesting the decision to cease nuclear production has contributed to more deaths than the accident itself.
Keywords: I12; K32; Q41; 330; precuationary principle; nuclear energy; electricity; mortality